Development of Gamification Learning Media Based on Google Sites Website for Technical Drawing Projection Material in Vocational Schools - Mukhadik, Fahrul; Wijanarko, Dwi; Qudus, Nur (Universitas Negeri Semarang, 2023)
The conventional use of media induces boredom among students, largely due to the limited exploration of creativity among teachers in crafting innovative and engaging learning materials using digital technology in teaching and learning processes. One application of digital technology involves developing gamification media based on the Google Sites website for technical drawing projection material in 10th grade in SMK. This research applies the Research and development (R&D) method. The research design chosen was the ADDIE model, which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The unit of analysis for this research is the development of gamification learning media based on the Google Sites website. The instruments used in this research were (1) assessment sheet and (2) feasibility questionnaire. The validity of the assessment sheet is obtained from CVR calculations and reliability using the ICC formula. The validity of the effectiveness questionnaire uses rcount and reliability uses the Cronbach's Alpha formula. The data analysis used in this research is (1) categorical to determine the level of eligibility; (2) and N-Gain difference test using the t test. The research results show that the feasibility test for responses from media experts and material experts is very feasible, while the effectiveness test is quite effective and significant in increasing student understanding. Therefore, it can be concluded that the development of gamification learning media on the Google Sites website can improve understanding among the students.